The Prognostic Factors for Locally Advanced cervical Cancer Patients Treated by Cisplatin Based Concurrent Chemoradiotherpy- A Retrospective Study - S. Jeeva; V. Arun Ramanan; Sowmiya. KR; P. Balasubramaniam; Dr Vidya; Dr Chandralekha (Asian Journal of Medical Research, 2019)
Background: Aim: To identify the prognostic factors for the locally advanced cancer cervix patients treated with weekly cisplatin based concurrent chemoradiation. Subjects and Methods: We have analyzed 57 women with FIGO stage IB2-IIIB cervical cancer treated in the Oncology outpatient department of a tertiary care center between May 2014 to December 2016.Inclusion criteria includes patients treated with Radical Radiotherapy with cisplatin 30mg/m2.Median total dose to point A was 72Gy. Data regarding age, performance status, stage, histology, grade, tumour size, pretreatment haemoglobin level, radiological imaging details, pelvic nodal involvement, compliance to treatment, no. of chemotherapy cycles, total duration of radiotherapy and toxicity profiles are reviewed from medical records. Primary endpoints were to assess the prognostic factors that affects the tumor response and progression free survival and disease free survival. Survival analysis was estimated using the Kaplan-Meier method and multivariate Cox proportional hazard model, to estimate the hazard ratio and 95% confidence intervals using IBM SPSS statistical software. Results: The median follow-up time was 18 months. The 2 year overall survival was 31.6% and PFS is 29.8%. In univariate analysis presence of pelvic node, tumor size, radiotherapy treatment duration, no. of chemotherapy cycles were significantly associated with overall survival and progression free survival. In multivariate analysis, only tumour size and radiotherapy treatment duration significantly affected the overall survival and progression free survival. Conclusion: Bulky tumour and prolongation of treatment duration were poor prognostic factors for patients with locally advanced cervical cancer. Chemotherapy with a high cumulative dose of cisplatin tended to result in better survival.